2016
DOI: 10.17344/acsi.2015.1421
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolics, anthocyanins, antioxidant and pro-oxidant activity of some red fruits teas

Abstract: Fruits represent one of the main dietary sources of bioactive compounds. Due to their remarkable health benefits, many functional foods of fruit origin, including fruit teas, are present on the market and there is an increased interest regarding the investigation of their nutritional parameters and quality. The aims of our study were: 1) to determine the total phenolic content (TPC), total anthocyanins content (TAC), antioxidant activity (AA), the scavenging capacity (IC50), the pro-oxidant activity (Pro-ox) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
2
8
1
1
Order By: Relevance
“…Figure 4 demonstrated that no significant difference ( p > .05) was shown between the TPC of hawthorn berry tea supplemented with and without the addition of probiotics (1,908.1–2,207.3 mg GAE/100 g sample) on the day of treatment (week 0). The obtained TPC values were comparable to blueberry tea (23.23 mg GAE/g blueberry tea) and raspberry tea (15.84 mg GAE/g raspberry tea) (Moldovan et al., 2016). According to Jurikova et al.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 4 demonstrated that no significant difference ( p > .05) was shown between the TPC of hawthorn berry tea supplemented with and without the addition of probiotics (1,908.1–2,207.3 mg GAE/100 g sample) on the day of treatment (week 0). The obtained TPC values were comparable to blueberry tea (23.23 mg GAE/g blueberry tea) and raspberry tea (15.84 mg GAE/g raspberry tea) (Moldovan et al., 2016). According to Jurikova et al.…”
Section: Resultssupporting
confidence: 58%
“…of probiotics (1,908.1-2,207.3 mg GAE/100 g sample) on the day of treatment (week 0). The obtained TPC values were comparable to blueberry tea (23.23 mg GAE/g blueberry tea) and raspberry tea (15.84 mg GAE/g raspberry tea) (Moldovan et al, 2016). According to Jurikova et al (2012) and Wu et al (2015), the major phenolic compound found in the hawthorn berry is epicatechin, chlorogenic acid, isoquercitrin, procyanidin, and ursolic acid.…”
Section: Gg During Storagementioning
confidence: 52%
“…Recent literature reports reveal that plant-based natural compounds of Brassica oleracea L. var. sabauda [47], red fruits teas [48], Salicornia herbacea L. [49], vegetables and agricultural by-products [50], ascorbic and humic acids [51], Raphanus sativus var. niger [52], green tea [53], and eugenol [54] display both antioxidant and prooxidant behaviours under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds could be ameliorated by chemical modifications (31). Epigallocatechin gallate (EGCG), a major component of green tea, is known to have many biologic activities including anti-oxidation, anti-inflammation, and anti-bacterial/viral infections (32)(33)(34)(35)(36)(37). GA, a part of EGCG, was shown to have inhibitory effects on mast cell-mediated allergic inflammation in our previous studies, and we have generated various derivatives of GA to improve its pharmacological effectiveness (10,11).…”
Section: Discussionmentioning
confidence: 99%